KARAKTERISTIK EKSTRAK BUAH BELIMBING WULUH (Averrhoa Bilimbi Linn) PADA PERLAKUAN PELARUT ETANOL DAN SUHU EKSTRAKSI - Sitompul, Yemima Maria Lasma Roha; Wartini, Ni Made; Sugitha, I Made (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2023)
Wuluh starfruit is a type of plant that contains a lot of acid. In addition to containing acid, starfruit also contains bioactive compounds such as polyphenols, flavonoids, alkaloids, saponins, and tannins that have the potential to inhibit bacterial activity. This study aims to determine the effect of ethanol solvent concentration and extraction temperature on the characteristics of the wuluh starfruit extract, to determine the best concentration of ethanol solvent and extraction temperature to produce wuluh starfruit extract. The experiment was a factorial experiment with two factors, designed using a randomized block design. Factor I is the concentration of ethanol solvent consisting of two types, namely ethanol 96% and ethanol 70%. Factor II is the extraction temperature which consists of 3 types, namely 30 o C, 40 o C, and 50 o C. The data were analyzed using analysis of variance and further tests were carried out with Honest Significant Differences. The results showed that the concentration of ethanol solvent and extraction temperature and their interactions affected the yield, total flavonoids, total tannins, and total acid,. The highest yield, total flavonoids, tannins and acids were shown in the treatment with 96% ethanol concentration and 30°C extraction temperature. The conclusion of this study is that the treatment with 96% ethanol solvent concentration and 30°C extraction temperature is the best treatment to obtain wuluh starfruit extract with the characteristics of a yield of 71%, total flavonoids 7.10%, total tannins 0.914 mg QE/g, and total acid 34,24%.